Using senses to encourage head and upper limb voluntary movement in young infants: Implications for early intervention. (2nd September 2016) - Al-Whaibi, Reem M.
Abstract: Primary objective : It has long been suggested that a neonate's movement and responses to external stimuli are the product of reflexive reactions rather than purposeful movements. However, several studies have demonstrated that this is not the case. Rationale of literature included : This study seeks to review reports showing that sensory stimuli resulted in newborns recognising and responding to different stimuli with active head or upper limb movements. We also discuss this in the context of current literature about early training on the advancement of movement and brain development. Results and outcomes : Taken together, it is clear that early active experience shapes learning in newborns. Conclusions : The impact of this research is most exciting for applications that would induce infants to make purposeful movements, especially as a means for early intervention and rehabilitation for the treatment of infants with or at high risk for developmental delay.